2008
DOI: 10.1111/j.1469-7580.2007.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal lung and metabolic development in two marsupial and four eutherian species

Abstract: Two marsupial species ( Monodelphis domestica, Macropus eugenii ) and four eutherian species (Mesocricetus auratus, Suncus murinus, Tupaia belangeri and Cavia aperea ) were examined to compare and contrast the timing of lung and metabolic development during the postnatal maturation of the mammalian respiratory apparatus. Using light, scanning and transmission electron microscopy, the lung structural changes were correlated with indirect calorimetry to track the metabolic development. Marsupial and eutherian sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 58 publications
(125 reference statements)
4
66
0
2
Order By: Relevance
“…In altricial species, the lungs are characterized by a well-developed bronchial system, which terminates in small sacs ( Table 2). The septa between the terminal sacs have a double-capillary net with a small amount of interstitium, so that they appear relatively thin (Szdzuy et al, 2008). Postnatal lung development is rapid and the formation of alveoli starts in Mesocricetus auratus at the age of 2 days (Szdzuy, 2006), in Suncus murinus and Rattus rattus at 4 days (Burri, '74;Szdzuy, 2006), and in Mus musculus at 5 days (Ten Have-Opbroek, '80).…”
Section: Placentaliamentioning
confidence: 99%
See 1 more Smart Citation
“…In altricial species, the lungs are characterized by a well-developed bronchial system, which terminates in small sacs ( Table 2). The septa between the terminal sacs have a double-capillary net with a small amount of interstitium, so that they appear relatively thin (Szdzuy et al, 2008). Postnatal lung development is rapid and the formation of alveoli starts in Mesocricetus auratus at the age of 2 days (Szdzuy, 2006), in Suncus murinus and Rattus rattus at 4 days (Burri, '74;Szdzuy, 2006), and in Mus musculus at 5 days (Ten Have-Opbroek, '80).…”
Section: Placentaliamentioning
confidence: 99%
“…The entirety of the numerous small alveoli provides a large gasexchange surface area. The alveoli are separated by a thin single-capillary septum, which is characteristic for the alveolar stage (Szdzuy et al, 2008). The newborn Cavia aperea and Macroscelides proboscideus are two typical representatives of this precocial lung type (Szdzuy, 2006 (Moore,'77), and presumably in other large species, this process occurs over a much longer period than in small eutherians (Baudinette et al,'88).…”
Section: Placentaliamentioning
confidence: 99%
“…The surge of catecholamines associated with the stress of parturition generally results in newborns having a higher massspecific V O2 (Bartlett and Areson, 1977;Mortola, 2001), with V O2 decreasing markedly within the first 24h after birth (Noblet and Le Dividich, 1981;Stewart et al, 1984). While previous studies have demonstrated the absence of this increased mass-specific metabolic rate in neonatal marsupials (Singer et al, 1995;MacFarlane and Frappell, 2001;Szdzuy et al, 2008), these studies were not concentrated on young in the first hours of life, where the newborn may have just recently attached to a teat and not yet fully settled. In addition to our newborn dunnarts, a hypometabolism during hypercapnia has also been described in the P5 opossum, albeit in conjunction with a hyperpnoea .…”
Section: Hypometabolism During Hypercapnia: a Novel Strategymentioning
confidence: 97%
“…Newborn Eutheria, on the other hand, feature a wide range of developmental stages, from altricial to precocial development, but they are always more advanced in development than marsupial neonates and undergo a rapid postnatal development ( Fig. 1C) (Hughes and Hall, 1998;Szdzuy, 2008;Szdzuy et al, 2008).…”
mentioning
confidence: 99%